Crowdsourcing Platform Toward Seismic Disaster Reduction: The Taiwan Scientific Earthquake Reporting (TSER) System - Liang, Wen-Tzong; Lee, Jian-Cheng; Hsiao, Nai-Chi (Frontiers in Earth Science, 2019)
We initiated an earthquake reporting project in 2016 to collect field observations of ground damages caused by large earthquakes from trained volunteers and interested citizens. After a potentially damaging earthquake occurs in the Taiwan area, our system, the Taiwan Scientific Earthquake Reporting System (TSER), would send a notice to the participants, who are encouraged to visit the epicentral area to survey and describe as in detail as possible the variations of the ground damages using a Usahidi-based mapping platform. They may also upload relevant images in the field when the condition permitted (i.e., good mobile signal). This collective information will be shared with the public after a quick check by the on-duty scientists. Statistically in Taiwan, damaging inland earthquakes, e.g., magnitude greater than 6, occurred every 2-3 years. During the intermittent time, the platform serves to share educational materials such as pictures of geological structures and landscapes, which are beneficial to many of the volunteers, who are high school science teachers. This experimental, science-oriented crowdsourcing system was first tested during the February 6, 2018 Mw 6.4 offshore Hualien, Taiwan earthquake. We received 19 field reports in the first 3 days after the earthquake. Most of these reports provide surface damage details along the Milun fault, which also ruptured during the 1951 ML 7.1 Longitudinal Valley earthquake sequence. The crowdsourcing approach of TSER has proven to be effective in enhancing public awareness and the potential for scientific advancement in hazard mitigation.